The Impact of Consumer Reviews in Buying Behavior: A Case of Kathmandu - Rupakheti, Upasana; Dahal, Gangadhar (Nepalese Journal of Economics, 2025)
This study examines the impact of consumer reviews in buying behavior: A case of Kathmandu. Consumer buying behavior is the dependent variable. The selected independent variables are product review quality, product review quantity, source of review, review consistency, and reviewer credibility. The primary source of data is used to assess the opinions of respondents regarding product review quality, product review quantity, source of review, review consistency, reviewer credibility, and consumer buying behavior. The study is based on the primary data of 126 respondents. To achieve the purpose of the study, a structured questionnaire was prepared. The correlation and multiple regression models are estimated to test the significance and importance of the impact of consumer reviews in buying behavior: A case of Kathmandu. The study showed a positive impact of product review quality on consumer buying behavior. It indicates that higher the product review quality, higher would be the consumer buying behavior. Similarly, the study showed a positive impact of product review quantity on employee commitment. It indicates that total number of reviews or ratings that a product leads to influence the consumer buying behavior. Likewise, the study also revealed a positive impact of source of review on consumer buying behavior. It indicates that authentic source of review leads to increase in consumer buying behavior. Further, the study observed a positive impact of review consistency on consumer buying behavior. It indicates that higher the consistency in review of the products, higher would be the consumer buying behavior. In addition, the study observed a positive impact of review credibility on consumer buying behavior. It indicates that higher the credibility of the contents of the reviews, higher would be the consumer buying behavior.